O34 Binge drinking, smoking and experience of intimate partner violence among women aged 16–44 years attending sexual health clinics. (8th June 2017) - Edelman, Natalie; Whetham, Jennifer; Mercer, Catherine; Cassell, Jackie; Visser, Richard de
Abstract : Introduction: BASHH guidance includes assessment of smoking history, intimate partner violence and alcohol risk in Sexual Health (SH) clinics. As part of a study assessing psychosocial predictors of sexual risk among women of reproductive age, we investigated the prevalence of these issues and their associations with sexual risk. Methods: A convenience sample of women aged 16–44 years attending a busy urban integrated Contraception and Sexual Health clinic was invited to complete a questionnaire about socio-demographic, sexual behaviour and psychosocial factors. Results: Of n=532 eligible women 44.5% were aged 16–24 years. 42.1% of participants reported binge-drinking (6+ units on one occasion) on a weekly basis. 36.7% reported currently smoking cigarettes or roll-ups. Using an adapted HITS domestic violence (DV) measure, 16.1% were classified as currently or previously experiencing DV. None of these factors was associated with reported risk of unintended pregnancy in the last 6 months. Multiple partnerships in the last year was not associated with DV experience (p=0.187) but remained positively associated, after adjustment for age, with current weekly binge-drinking (adjusted odds ratio = 2.13) and with current smoking (AOR =1.87). Discussion: Findings suggest that interventions for binge-drinking, cigarette smoking and DV may be warranted for a substantial minority of women attending SH clinics. In particular observed associations between binge-drinking, cigarette smoking and multiple partnerships may point towards broader lifestyle choices that could be addressed concomitantly in SH clinics to help reduce sexual risk behaviour.